Public knowledge, belief, and preventive practices regarding dengue: Findings from a community-based survey in rural Bangladesh. - Rajon Banik; Md Saiful Islam; Mahfuza Mubarak; Mahmudur Rahman; Hailay Abrha Gesesew; Paul R Ward; Md Tajuddin Sikder (Public Library of Science (PLoS), 2023)
Background Dengue fever, the most prevalent mosquito-borne viral infection, is a recurrent public health threat in Bangladesh. Despite the government's efforts, dengue outbreaks are on the upswing, and people's knowledge, belief, and preventive practices regarding the disease at the rural community level are unclear. Objective The objective of this study was to assess the level of knowledge, belief and preventive practices regarding dengue and associated factors among community people from rural Bangladesh. Methods A cross-sectional survey was conducted involving 401 people using a convenient sampling technique from three unions of Savar from August to September 2021. Participants' responses were collected through face-to-face interviews using a pre-tested structured questionnaire that included information related to socio-demographics, dengue-related knowledge, preventive practices, and the health belief model (HBM) constructs. Multiple linear regression analysis was performed to determine the factors associated with the knowledge and preventive practices of dengue. Results Overall, participants (mean age = 33.47 ± 12.96 years; age range = 18-75 years) correctly answered 66.15% of the knowledge questions regarding dengue. Higher education, travel to dengue-risk regions, and self-efficacy under the HBM construct were all shown to be strongly associated with dengue knowledge. Regarding HBM constructs, about 80% of the participants perceived dengue as dangerous, but less than half (41.4%) believed themselves susceptible to dengue. Considering perceived barriers, 73.07% of the participants believed their residential area was not suitable for Aedes mosquito breeding. Nearly all (93.52%) believed they always kept their surrounding area clean as part of self-efficacy. Moreover, on average participants engaged in 53.69% of all dengue preventive practices. Being older, female, having a higher education, being a service holder, having a good quality of house structure, and perceived susceptibility as well as self-efficacy under the HBM construct were all factors in participants' dengue prevention activities. Participants' dengue preventative practices were shown to be significantly influenced by their knowledge. Conclusions The findings of this study found a moderate level of knowledge regarding dengue among the participants. Regarding dengue prevention, although participants scored highly in several indicators, the overall preventive practices were not satisfactory. This suggests that there is a pressing need for expanded education outreach aimed at increasing public awareness of dengue and encourage preventive practices within rural communities in Bangladesh.